Understanding the Roles of Green Awareness and Green Brand Image in Shaping Eco-Friendly Consumer Decision-Making: A Theoretical Synthesis - Pahrul; Mahmuddin (International Journal of Education, Vocational and Social Science, 2025)
This theoretical review examines how Green Awareness and Green Brand Image jointly influence eco-friendly consumer decision-making. Drawing on recent literature, the study synthesizes cognitive and perceptual mechanisms that guide consumers in evaluating sustainable products. The review finds that Green Awareness strengthens consumers’ understanding of environmental issues, while Green Brand Image provides credibility cues that build trust and reduce uncertainty. Together, these constructs interact synergistically to motivate eco-friendly purchase decisions. However, challenges such as greenwashing, socio-economic constraints, and cultural differences may weaken this relationship. The review contributes to sustainability marketing theory by offering an integrated conceptual understanding and outlining directions for future research.